Media Sosial sebagai Pendukung Jaringan Komunikasi Politik - Priadji Priadji; Udi Rusadi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
ABSTRACT Individual and group interactions are facilitated by advances in information and communication technology. The state does not fully regulate the flow of communication and news to the general public. Social media that has the ability to disseminate information can be used by messengers to persuade, inspire, and take the desired action. At the same time, the power of the mainstream media is eroding. The aims of this study were to: (1) characterize social media users regardless of their socioeconomic status or political affiliation; (2) examine efforts to reach audiences through social media and traditional media; and (3) recommend future research. (3) investigate the role of social media in democracy as a promoter of parliamentary network technology. To present a comprehensive picture of social media in relation to the political communication networks used by people, organizations and other political institutions, this study uses a qualitative approach. According to the research findings, participants were not constrained by their social, economic or political position. They also differ from conventional mass media in the way they reach audiences and promote the connectivity of political networks in democracies. Keywords: Social media, Traditional media, Online political networks, State democracy